PENGARUH TINGKAT PENDIDIKAN, PERTUMBUHAN EKONOMI DAN INVESTASI TERHADAP TINGKAT PENGANGGURAN ANTAR KABUPATEN/KOTA DI PROVINSI SUMATERA BARAT - Monica Wulandari; Marwan Marwan (Universitas Negeri Padang, 2019)
The purpose of this study for know does the level of education , economic growth and investment have a significant effect the unemployment rate between district/city in West Sumaera. This research use the panel data views of the 12 districts and 7 cities in West Sumatera Province start the year 2013 to 2017 gathered from Statistics Indonesia West Sumatera. This study used a Random-effect Model (REM). The research results obtained are (1) Together the level of education, economic growth and investment significant effect against the unemployment rate between districts/city in West Sumatera. (2) the level of educatio is positive and has no significant effect against the unemployment rate between districts/city in West Sumatera. (3) economic growth is negative and has a significant effect the unemployment rate between districts/city in West Sumatera. (4) Investment is negative and has significant effect the unemployment rate between districts/city in West Sumatera.Keywords : education, economic growth, investment, unemployment